Accurate prediction of the linear viscoelastic properties of highly entangled mono and bidisperse polymer melts - Stephanou, Pavlos S.; Mavrantzas, Vlasis G. (My University, 2014)
We present a hierarchical computational methodology which permits the accurate prediction of the linear viscoelastic properties of entangled polymer melts directly from the chemical structure, chemical composition, and molecular architecture of the constituent chains. The method entails three steps: execution of long molecular dynamics simulations with moderately entangled polymer melts, selfconsistent mapping of the accumulated trajectories onto a tube model and parameterization or finetuning of the model on the basis of detailed simulation data, and use of the modified tube model to predict the linear viscoelastic properties of significantly higher molecular weight (MW) melts of the same polymer. Predictions are reported for the zero-shear-rate viscosity η0 and the spectra of storage G′(ω) and loss G″(ω) moduli for several mono and bidisperse cis- and trans-1,4 polybutadiene melts as well as for their MW dependence, and are found to be in remarkable agreement with experimentally measured rheological data. © 2014 AIP Publishing LLC.
Keywords: Polybutadienes; Viscoelasticity; Digital storage; Molecular dynamics; Tubes (components)